Work productivity in rheumatoid arthritis patients from two Latin American countries treated with tofacitinib or biological DMARDs. (4th July 2022) - Gutierrez-Ardila, MV; Reyes, Jm; Madariaga, H; Otero, W; Guzman, R; Izquierdo, J; Abello, M; Velez, P; Castillo, D; Ponce de Leon, D; Lukic, T; Amador, L
ABSTRACT: Objective: To evaluate work productivity of adult Latin American patients with rheumatoid arthritis (RA) treated with tofacitinib and biological disease-modifying anti-rheumatic drugs (bDMARDs) measured by the Work Productivity and Activity Impairment (WPAI) in RA questionnaire at 0- and 6-month follow-up. Methods: This non-interventional study was performed in Colombia and Peru. Evaluated the effects of tofacitinib and bDMARDs in patients with RA after failure of conventional DMARDs. The WPAI-RA questionnaire was administered at baseline and at the 6-month (±1 month) follow-up. The results are expressed as least squares means (LSMs), and standard errors (SEs). Results: One hundred patients treated with tofacitinib and 70 patients treated with bDMARDs were recruited. Twenty-eight percent of patients from the tofacitinib group and 40.0% from the bDMARDs group were working for pay at baseline. At month 6, the changes in absenteeism, presenteeism, and work impairment due to health were −18.3% (SE 7.7), −34.8% (SE 5.9), and −11.0% (SE 16.5), respectively, in the tofacitinib group and −19.4% (SE 8.0), −34.8% (SE 6.2), and −15.9% (SE 15.0), for the bDMARD group. Conclusion: For patients who reported working, there were improvements in presenteeism, absenteeism, and work impairment due to health in both groups. Trial registration: NCT03073109